Comprehensive study on corrosion protection properties of Al2O3, Cr2O3 and Al2O3–Cr2O3 ceramic coatings deposited by plasma spraying on carbon steel - Zamani, Pejman; Valefi, Zia; Jafarzadeh, Kourosh (Ceramics international, 2022)
In this study, individual Al2O3 and Cr2O3 coatings and Cr2O3-25, 50, 75 wt% Al2O3 composite coatings were applied on carbon steel by atmospheric plasma spraying method. Corrosion experiments were performed on as-sprayed and epoxy resin sealed coatings including potentiodynamic polarization, electrochemical impedance spectroscopy and long-term immersion in 3.5 wt% NaCl solution. Phase composition and microstructure of the coatings were investigated by x-ray diffraction, optical microscopy and scanning electron microscopy, before and after the corrosion experiment. The results showed that the Cr2O3 coating exhibited the best corrosion resistance, due to the densest microstructure and highest adhesion strength. The Cr2O3-25 wt% Al2O3 coating had the highest interconnected porosities and thus had the least corrosion resistance compared to other coatings. In general, the as-sprayed coatings induced a maximum increase of 3.93 times the polarization resistance (Rp) in the polarization experiment and a 3.5 times increase in the charge transfer resistance (Rct) in the EIS experiment, which was not significant. Stresses caused by increased volume of corrosion products in the coating-substrate interface resulted in the spallation of Cr2O3-25, 50 wt% Al2O3 coatings from the substrate over long-term of immersion. The adhesion strength of the coatings was a determining criterion for the long-term durability of the coatings. The sealing treatment resulted in a significant increase in Rp and Rct.